Collateralized debt obligations : structures and analysis - Goodman, Laurie S.; Fabozzi, Frank J. (Hoboken, N.J. : J. Wiley & Sons, 2002)
The book covers Cash flow versus market value structures, Synthetic structures, Structures backed b speculative and investment grade corporate bonds and loans, emerging market bonds, and structured finance products.
Second series statement on jacket.
Includes bibliographical references and index.
gau 21/05/14
Loans
Keywords: Debt; Asset-backed financing